Memadukan Konsep Kecerdasan Intelektual, Emosional, Spiritual dan Ruhaniah Dalam Proses Pendidikan - Junanah - (Islamic University of Indonesia, 2002)
The integrated educational system is an alternative in overcoming problems of the educational which are dualistic. The intention is integrating of the IQ (Intelligent Quotiens), EQ (Emotional Quotiens), SQ (Spiritual Quotient), and TQ (Trancedental Quotiens). To develop this model, we need a school which supported by a good teacher, and school management completely, otherwise, it could be fallen.Key Word: The integrated educational system, Intelligent Quotiens, Emotional Quotiens, Spiritual Quotiens, Trancedental Quotiens